New Phosphorylating Agents for the Synthesis of Phosphatidylethanolamines - Tsubaki, Kouta; Yamanaka, Tomoki; Hisamitsu, Takuya; Shimooka, Hirokazu; Kitamura, Mitsuru; Okauchi, Tatsuo (Synthesis, 2021)
The preparation of three novel phosphorylating agents and their application toward the synthesis of phosphatidylethanolamines is described. These reagents are stable to air and moisture, and phosphorylate glycerols in good yield. The experimental procedures using these phosphorylating agents are simple. Moreover, the appropriate reagent can be selected based on the desired functional groups of the targeted phosphatidylethanolamine.
Keywords: phosphorylation; phosphatidylethanolamines; transesterification; glycerophospholipids; dialkyl 2,2,2-trifluoroethyl phosphates